Elimination of inrush current in parallel transformers by sequential phase energization - Basu, K. P.; Asghar, Ali; Morris, Stella (IEICE-INST ELECTRONICS INFORMATION COMMUNICATIONS ENG, 2007)
Production of very high inrush currents in transformers during energization may create deep voltage sag causing malfunction to electronic and other loads. In high voltage power system star-delta transformers are generally switched in, one by one, producing inrush currents each time. The inrush current may be reduced by sequential phase energization of each transformer with neutral resistors.